Reading Comprehension through the FIVES Model and Guided Reading Model to Improve Critical Thinking Ability in the Industrial Revolution Era 4.0 - Supriatna, Irfan; Agusdianita, Neza; Yuliantini, Nani; Herman, Herman; Resnani, Resnani (Mimbar Sekolah Dasar, 2020)
Elementary students' critical thinking skills are one of the components developed in 21st Century learning. However, these critical thinking skills are still very shallow and far from expectations. It was proven by the results of international surveys that show low average scores. Likewise, the results of the pretest critical thinking skills of fifth-grade students in 2 elementary schools in Sukabumi Regency showed a low average value. This study aims to determine the increase in students' critical thinking skills in learning to read comprehension through the use of the FIVES Model and Guided Reading Model in the Industrial Revolution Era 4.0. The research method uses quasi-experimental with Static Group Pretest-Postest Design. The subject of the research was fifth-grade elementary school students. SDN 4 Cicurug implements the FIVES Model, and SDN 2 Purwasari implements the Guided Reading Model. The results showed that the use of these two models could improve the critical thinking skills of elementary students. However, the increase in students' critical thinking skills through the FIVES Model compared to the Guided Reading Model in reading comprehension in the Industrial Revolution Era 4.0.